The synthesis of "BCN" diamond materials with different B/N additives under high pressure and high temperature. (September 2016) - Sun, Shishuai; Cui, Wen; Jia, Xiaopeng; Ma, Hong-an; Lv, Jiang
Abstract: The diamond crystals co-doped with B and N atoms were prepared under high pressure and high temperature (HPHT) to synthesize "BCN" diamond material. The two kinds of "BCN" diamond materials with different additives have been synthesized, corresponding to the h-BN, NaN3 and B powder systems, respectively. The results showed that the synthesized "BCN" diamonds from h-BN additive are strip-shaped diamonds. However, when the boron and nitrogen sources from NaN3 and B powder additives were used, the synthesized "BCN" diamonds had traditional hex-octahedron shapes with non-uniform colors. The results of FTIR and XPS showed that there is stronger BN bonding in the "BCN" diamonds obtained from Fe–Ni–C–h-BN system than the Fe–Ni–C–NaN3 –B system under the synthesis conditions used in these experiments. The changes of the crystallization medium caused by the different B and N source additives resulted in the difference both of synthesis conditions and characteristics of the synthesized "BCN" diamond crystals, leading to the results of our observation. Highlights: Two kinds of "BCN" diamond materials with different additives have been synthesized under HPHT. The "BCN" diamonds synthesized from different additive systems show different morphologies and colors, sizes. The results of FTIR and XPS spectrum indicate bonding between B, C and N of "BCN" diamonds from different additives.